2022
DOI: 10.2196/35053
|View full text |Cite
|
Sign up to set email alerts
|

Emerging Artificial Intelligence–Empowered mHealth: Scoping Review

Abstract: Background Artificial intelligence (AI) has revolutionized health care delivery in recent years. There is an increase in research for advanced AI techniques, such as deep learning, to build predictive models for the early detection of diseases. Such predictive models leverage mobile health (mHealth) data from wearable sensors and smartphones to discover novel ways for detecting and managing chronic diseases and mental health conditions. Objective Curren… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
32
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(33 citation statements)
references
References 102 publications
1
32
0
Order By: Relevance
“…For example, some studies have proposed adapting reinforcement learning algorithms in mHealth trials to sophisticate and personalise intervention policies over the trial period 46,47 . Incorporating artificial intelligence into mHealth (AI-powered mHealth) 48 Corresponding to the findings in the analyses of the proximal effect, whole effect analyses showed stabilised sleep hours and improved PSQI total scores after study 2, especially in group B. Thus, in this study, we demonstrated the distal effects of sleep JITAI on sleep stability and subjective sleep quality.…”
Section: Discussionsupporting
confidence: 67%
“…For example, some studies have proposed adapting reinforcement learning algorithms in mHealth trials to sophisticate and personalise intervention policies over the trial period 46,47 . Incorporating artificial intelligence into mHealth (AI-powered mHealth) 48 Corresponding to the findings in the analyses of the proximal effect, whole effect analyses showed stabilised sleep hours and improved PSQI total scores after study 2, especially in group B. Thus, in this study, we demonstrated the distal effects of sleep JITAI on sleep stability and subjective sleep quality.…”
Section: Discussionsupporting
confidence: 67%
“…It is almost impossible to present all the areas in which AI is applied in medicine today, therefore this paper will present only some of them. Only 15 or 20 years ago, the application of AI in medicine was mostly experimental and geographically limited to developed and rich countries ( 11 18 ). Today, AI can be used in a variety of ways to improve healthcare and medicine:…”
Section: Artificial Intelligence In Medicine and Healthcarementioning
confidence: 99%
“…Such mobile health (mHealth) interventions are increasingly used to encourage healthy eating behaviors [7][8][9][10], and are increasingly popular among young users [11,12]. mHealth technologies already play a significant role in reshaping healthcare access [13,14] and allow for broad access to scalable and cost-effective solutions [8]. AI-based services are an emerging trend [15,16], with an increasingly substantial impact on various healthcare domains, providing enhanced accuracy, improved outcomes, and cost-effectiveness [17][18][19], and healthcare professionals have been found to hold favorable views toward AI [20,21].…”
Section: Introduction Backgroundmentioning
confidence: 99%